Input lokasi sakral dan tempat penting masyarakat adat dalam tata ruang Provinsi Papua sebagai kawasan cagar budaya - Watopa, Yoseph; Moeljono, Soetjipto; Wamafma, Bastian; Rahmawan, Fajar; Nathalis Kolop, Delizius; Korwa, Godlif (Program Pascasarjana Universitas Papua, 2025)
ABSTRAK: The Indigenous population in Papua has employed a zoning system for land usage as a method of spatial planning. The zoning system categorises spaces into hunting and returning zones, permanent hunting zones, gardening zones, fishing zones, crocodile egg-laying zones, sacred zones, sago hamlet zones, customary protected zones, and residential zones. The geographical organisation of these indigenous communities was derived from the participatory mapping technique of traditional territories. The outcomes of the participatory mapping were categorised and analysed geospatially, using vector data analysis from thematic maps of natural resource utilisation through the amalgamation of features of the same type with varying lines and polygons. The selection of vector data employs the select by attribute approach, and the outcomes are included into the Papua Province Spatial Plan (RTRW) focussing on land cultural heritage regions. The area of customary lands identified by participatory mapping is 2,201,311 hectares. In the Papua Province RTRW 2023-2043, 8,778.50 hectares are classified as a cultural heritage land area